Bacillus cereus in fresh ricotta: Comparison of growth and Haemolysin BL production after artificial contamination during production or post processing. (September 2017) - Tirloni, Erica; Ghelardi, Emilia; Celandroni, Francesco; Bernardi, Cristian; Casati, Riccardo; Rosshaug, Per Sand; Stella, Simone
Abstract: Bacillus cereus is of particular concern for the production of fresh ricotta, due to the ability of spores to survive to the thermal treatment, leading to a potential germination, growth and toxin production in the product. This study aimed to evaluate the effect of a B. cereus contamination occurring in the whey used for the production of ricotta, or in the final product as post-production event. Four B. cereus strains (ATCC 14579 and three clinical isolates, GGu1, GPe2 and RCe1) were first evaluated for their ability to grow at different temperatures (from 5 to 55 °C) and spore survival rate to different thermal treatments (65, 70, 80 and 90 °C for 30, 15. 10 and 3 min, respectively). None of the strains showed to be psychrotrophic, as no growth below 10 °C was observed. Strains ATCC 14579 and GPe2 were the most resistant to thermal stresses and were selected for the inoculation tests. In the first trial, two aliquots of whey were inoculated with ATCC 14579 or GPe2 strain and used for the production of fresh ricotta samples, that were stored at 10 °C for 7 days (only GPe2) or 15 °C for 5 days (both the strains). In the second trial, the inoculation was made on fresh ricotta just after production. Samples were stored in the same conditions and analysed daily for the quantification of B. cereus vegetative cells and spores; the L2 component of Haemolysin BL was also quantified in the product. At 15 °C, a very fast germination of spores, followed by an active growth, was constantly observed in the two trials for both B. cereus strains. An earlier growth was detected in the whey-inoculated samples, suggesting the potential activation of spore germination caused by high temperatures reached during ricotta production. A slightly faster growth was observed for ATCC 14579 strain. At 10 °C, GPe2 strain showed a slow growth, with similar rates between whey- or product-inoculated ricotta samples. The production of HBL toxin was significant only in samples kept at 15 °C, starting from the 4th day of storage. In order to ensure the consumers' protection, these results suggest the suitability of fresh ricotta as a substrate for the growth and metabolic activity of B. cereus, highlighting the need to prevent the contamination of the product and, above all, to apply a correct refrigeration during its storage. Highlights: Two Bacillus cereus strains inoculated in ricotta at 15 °C showed a very fast growth. At 10 °C B. cereus strains showed a very low growth. An earlier growth of B. cereus was detected in the whey-inoculated samples. The production of HBL toxin was detectable in ricotta at 15 °C after 4 days storage.